2020
DOI: 10.1242/jeb.232322
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on metabolic scaling of a keystone freshwater crustacean depend on fish-predation regime

Abstract: According to the metabolic theory of ecology, metabolic rate, an important indicator of the pace of life, varies with body mass and temperature due to internal physical constraints. However, various ecological factors may also affect metabolic rate and its scaling with body mass. Although reports of such effects on metabolic scaling usually focus on single factors, the possibility of significant interactive effects between multiple factors requires further study. In this study, we show that the effect of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 165 publications
3
25
0
Order By: Relevance
“…Whether this variation in macroinvertebrate metabolic scaling slope is related to environmental factors, such as water temperature [58,59] and biological factors, such as predation pressure [60,61], is less known. Moreover, this variation of metabolic responses in relation to predation threats may be temperature-dependent [62,63]. These studies showed that smaller macroinvertebrates in both freshwater springs and saltwater lagoons more strongly increased their metabolism under high temperature and predation threat, when compared with the larger taxa.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)mentioning
confidence: 82%
“…Whether this variation in macroinvertebrate metabolic scaling slope is related to environmental factors, such as water temperature [58,59] and biological factors, such as predation pressure [60,61], is less known. Moreover, this variation of metabolic responses in relation to predation threats may be temperature-dependent [62,63]. These studies showed that smaller macroinvertebrates in both freshwater springs and saltwater lagoons more strongly increased their metabolism under high temperature and predation threat, when compared with the larger taxa.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)mentioning
confidence: 82%
“…Indeed, understanding how microevolutionary processes that occur within species lead to macroevolutionary trends across species presents a major challenge in the study of metabolic rates and their scaling with body size (Glazier, 2014a; Harrison, 2017; Koch et al., 2021; Pettersen et al., 2018). Many species with indeterminate growth can have relatively large body size ranges (Glazier et al., 2020); however, metabolic costs of growth may be difficult to isolate from the costs of maintenance (Jørgensen, 1988). Thus, species with determinate growth, where growth does not occur after sexual maturation, may provide avenues to more clearly identify maintenance costs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, body size is considered a key trait related to the community assembly processes of seagrass amphipods, being involved in a series of complex relationships occurring between the abiotic features of surrounding environment and direct and indirect biotic interactions, mainly due to competition and predation avoidance. Body size, temperature and salinity are dominant factors affecting the metabolic rate in amphipods (Poulin and Hamilton 1995; Maranhão and Marques 2003), which may however vary significantly in response to different ecological condition as, for instance, predation pressure (Glazier et al 2020). Moreover, historical and biogeographic processes, alongside current environmental conditions, may have played a role in determining the distribution and complexity of seagrass habitat ( sensu Hacker and Steneck 1990), thereby allowing for the functional differentiation of assemblages at bioregional scale as response to an evolved consequence of consistently high predation risk, size-dependent habitat selection and food availability (Kovalenko et al 2011; Lürig et al 2016).…”
Section: Discussionmentioning
confidence: 99%